Development of geodetic GPS infrastructure and its applications:the Malaysia experience - A. Kadir, Abd. Majid (2003)
Problems with classical Datum, Historically, Malaysian geodetic datums has been established since 19th century using conventional surveying techniques and procedures Confined to small areas of the globe, fit to limited areas and to satisfy national mapping requirements. Local datums are not aligned with global geocentric coordinates frames. Existing datum not compatible with the wide spread use of satellite positioning systems and international recommendation. Two separate geodetic datums ( Peninsular Malaysia and East Malaysia)